Analysis of the relationship between environmental particulate matter exposure and congenital diseases, as well as the epidemiological trends and burden of impact on newborns - Mulati Julaiti; Dilixiati Wubuli; Tingting Cui; Nadire Nijiati; Pengfei Huang; Bowen Hu (Ecotoxicology and Environmental Safety, 2025)
Background: With the rise in air pollution levels, there is a growing concern about its impact on public health, particularly on the development of fetuses and newborns. This study investigates the causal relationship between environmental particulate and congenital diseases in newborns, using a Mendelian randomization approach with GWAS data. Methods: The study employed Mendelian randomization, utilizing single nucleotide polymorphisms as instrumental variables, to estimate the causal effect of environmental Particulate on congenital diseases. Data from the UK Biobank and FinnGen databases were used to identify independent SNPs associated with environmental particulate. Two-sample Mendelian randomization methods were applied, and the Global Burden of Disease (GBD) database was leveraged to analyze the trends and burden of neonatal diseases from 1990 to 2021 and to forecast the burden for 2022–2052.Results: Significant causal associations were identified between PM2.5, PM10 and specific congenital malformations, including gallbladder, bile duct, liver anomalies, and malformations of the reproductive organs and broad ligaments. A review of GBD data indicates a decline in the prevalence of neonatal DALYs and YLDs attributed to ambient particulate matter over the past three decades. This may be attributed to improvements in air quality and the implementation of pollution control measures. However, forecasting models indicated potential future risks, suggesting that the burden of disease in newborns due to particulate matter exposure remains a concern.Conclusion: The study provides evidence of a causal link between environmental particulate and congenital diseases in newborns, highlighting the importance of air pollution reduction for the health of newborns. Despite the observed decline in disease burden, the potential future risks underscore the necessity for continued air quality management and the need for further research to understand the complex interactions between environmental particulate, genetic factors, and fetal development.